OPTIMIZED CONTROL OF THE PHYSICAL BATTERY SYSTEM - Van De, Pham (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Today, a significant issue for many nations worldwide is a shortage of energy. Renewable energy sources, particularly solar energy, are being investigated as additional energy sources to address the aforementioned issue. The high investment cost and poor performance of solar energy, however, provide the biggest challenge. This study only addresses the power optimization problem. It is suggested that the method used to determine the solar system's maximum power point modify incremental conductance. Adapted Incremental Conductance algorithm based on Incremental Conductance conventional techniques. The Modified Incremental Conductance method, however, has several exceptional advantages since it has a voltage change (V) that is not constant but fluctuates in an ideal manner to achieve the maximum power point as soon as possible. The voltage V is greater away from the peak power point while it is zero at the peak power point. Modified incremental conductivity algorithm to find peak power point faster than traditional algorithms. With maximum power point change reducing ambient power loss at the highest powers point. This helps to optimize voltage difference value.